2020
DOI: 10.3389/fvets.2020.00062
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity Assessment of Rift Valley Fever Virus Virus-Like Particles in BALB/c Mice

Abstract: Rift Valley fever (RVF) is an acute, febrile zoonotic disease that is caused by the RVF virus (RVFV) and is spread by arthropod vectors. Virus-like particle (VLP) vaccines, which have the advantages of strong immunogenicity and safety, play an important role in the prevention of this disease. VLPs for RVFV were successfully prepared by our research group using a baculovirus-insect cell expression system. To study the immunogenicity of these RVFV VLPs, a correct 3rd or 4th generation recombinant baculovirus, rB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Several live virally vectored subunit-RVFV vaccines, using replication-competent, i.e., Newcastle disease virus [16] and Capripox virus [17], and replication-defective adenovirus [18,19], and vaccinia virus Ankara (MVA) [20], have been developed. Further, baculovirus-expressed RVFV antigen-based subunit vaccines [21] and RVF virus-like particles vaccines [22] have also been developed and tested for vaccine efficacy against RVFV. However, each has its own deficiency concerning vaccine efficacy, safety, or booster requirements [13].…”
Section: Discussionmentioning
confidence: 99%
“…Several live virally vectored subunit-RVFV vaccines, using replication-competent, i.e., Newcastle disease virus [16] and Capripox virus [17], and replication-defective adenovirus [18,19], and vaccinia virus Ankara (MVA) [20], have been developed. Further, baculovirus-expressed RVFV antigen-based subunit vaccines [21] and RVF virus-like particles vaccines [22] have also been developed and tested for vaccine efficacy against RVFV. However, each has its own deficiency concerning vaccine efficacy, safety, or booster requirements [13].…”
Section: Discussionmentioning
confidence: 99%
“…At 14 days from the second immunization, 60% and 100% neutralization at 1:74 and 1:32 serum dilution, respectively, was observed using a RVFV pseudovirus neutralization assay. High levels of the IL-4 and IFN-γ cytokines were also induced by CD4 + and CD8 + T cells pointing to a balanced Th1/Th2 immune response in mice [133].…”
Section: Virus-like Particlesmentioning
confidence: 93%
“…VLPs made by transfecting 293T cells with the expression plasmids p18 subcloned with L, N and M segments and a reporter plasmid containing Renilla luciferase gene (Ren-Luc) [131] RVFV chimVLPs Chimeric VLPs containing RVFV Gn and Gc, nucleoprotein N, and the gag protein of Moloney murine leukemia virus [132] RVFV GnGc VLP VLPs generated through the expression of Gn and Gc in the Drosophila insect cell expression system [133] 2.1. Conventional Live Attenuated RVF Vaccines 2.1.1.…”
Section: Ren-vlpsmentioning
confidence: 99%
“…, Li et al (2016 used recombinant baculovirus to express RVFV NP and GP, which assembled into VLPs. They further explored the immunogenicity of these VLPs, and found that although T/B-cell responses were induced by VLPs, the responses were weaker than those stimulated with VLPs combined with Freund's adjuvant (Table 2) (Li et al, 2020). Chimeric VLPs containing RVFV NP, Gn and Gc, meanwhile including gag from retroviruses were also tested against RVFV, in which the protective efficacy of chimeric VLPs is superior to VLPs with NP and VLPs without NP, which suggests gag enhances the uniformity and quantity of VLPs and may also serve as an adjuvant (Table 2) (Mandell et al, 2010).…”
Section: Vlps/rlps Vaccinesmentioning
confidence: 99%